Michael S. Heiser, Angels: What the Bible Really Says About God’s Heavenly Host - Dylon, Barbara Ewelina (The Biblical Annals, 2019)
Book Review: Michael S. Heiser, Angels: What the Bible Really Says About God’s Heavenly Host (Bellingham, WA: Lexham Press, 2018) (Barbara Ewelina Dylon)